Emission controls of mercury and other trace elements during coal combustion in China: a review. Issue 5 (26th April 2018) - Zhao, Yongchun; Yang, Jianping; Ma, Siming; Zhang, Shibo; Liu, Huan; Gong, Bengen; Zhang, Junying; Zheng, Chuguang
ABSTRACT: Trace elements (TEs) in coal result in substantial pollutant emissions and cause serious damage to the ecological environment and human health in China. The emission and control of TEs, especially mercury, during coal combustion are of significant concern, and extensive studies have been performed in China in recent years. This paper reviews the emission characteristics and control strategies of mercury and other TEs during coal combustion in China. The occurrence of TEs in Chinese coals, including the average content of TEs in Chinese coals, the distribution of TEs in Chinese coals from different coal-forming periods, coal ranks, and coal-bearing regions are summarized. The emission characteristics of five specific TEs (Hg, As, F, Se, and Cr) during coal combustion in China are reviewed in detail. Effects of the coal type, combustion temperature, and combustion mode on the partitioning behaviour and emission characteristics of TEs are discussed. The effects of existing air pollution control devices of coal-fired power plants in China on the speciation and emission of TEs are discussed comprehensively. Various sorbents, such as activated carbon, fly ash, calcium-based sorbents, metal oxides, and mineral sorbents, used for TE removal are also summarized. Moreover, the removal performance of different sorbents for capturing certain TEs is compared comprehensively. Finally, future work for TE emission control in China is proposed.